Re-thinking Knowledge and Social Change in South Africa - (:unkn) unknown (My University, 2014)
The paper starts from the premise that twenty years after the transition to formal democracy in South Africa, the issue of the production and use of socially relevant knowledge and the role of progressive researchers in contributing to social change warrant renewed attention. The analysis centers on two issues. The first relates to different ways of interpreting the knowledge needs of the current conjuncture. The second concerns the relationship between knowledge, truth and truthfulness in the world of knowledge for policy. The paper argues for greater reflexivity about the current conditions for producing research for social change in a context increasing divided about what constitutes a good society.
Keywords: African Research